Nelson textbook of pediatrics - Kliegman, Robert M.; ST Geme, Joseph W.; Blum, Nathan J. (Elsevier, 2020)
This book is the reference of choice among pediatricians, pediatric residents, and others involved in the care of young patients. This fully revised edition continues to provide the breadth and depth of knowledge you expect from Nelson, while also keeping you up to date with new advances in the science and art of pediatric practice. From rapidly changing diagnostic and treatment protocols to new technologies to the wide range of biologic, psychologic, and social problems faced by children today, this comprehensive 2-volume reference keeps you on the cutting edge of the very best in pediatric care.